2021
DOI: 10.1111/os.12912
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Osteomyelitis in Adults: A Systematic Review

Abstract: The aim of this systematic review was to characterize the clinical features of adults with Salmonella osteomyelitis and summarize diagnosis and treatment methods to provide guidance for clinicians. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We conducted a literature search in the PubMed, EMBASE, and Cochrane Library databases. Article screening and data extraction were performed by two reviewers individually. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 22 publications
0
39
1
Order By: Relevance
“…Other common risk factors include lymphoma, diabetes mellitus, systemic lupus erythematosus, steroids, trauma, surgery and extremes of ages [ 5 ]. In a recent systematic review, cases in individuals without any apparent risk factors have been described as well [ 2 ]. Except for the fourth patient who was diabetic, the other three patients had no history of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other common risk factors include lymphoma, diabetes mellitus, systemic lupus erythematosus, steroids, trauma, surgery and extremes of ages [ 5 ]. In a recent systematic review, cases in individuals without any apparent risk factors have been described as well [ 2 ]. Except for the fourth patient who was diabetic, the other three patients had no history of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…has been due to non-typhoidal Salmonella . Of the 67 cases of Salmonella osteomyelitis in a systematic review, only 19 were found to be due to S. Typhi [ 2 ]. Cases due to S. Typhi and S. Paratyphi have been reported, mainly from developing countries [ 6–8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations